Guidance and Counseling Information Technology Module Based on Guided Discovery Learning - Ni Made Diah Padmi (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Skills in using information technology are an important requirement in this era. For this reason, it is necessary to prepare guidance and counseling students to have adequate skills in using various information technology applications. These skills are needed to meet students' needs according to technological developments. This research aims to test the feasibility of the developed module. This research belongs to the type of development research which was developed using the Borg & Gall model. The subjects involved in this study were media design experts and material experts. The data collection in the study was carried out using observation, interview, and questionnaire methods, with research instruments in the form of design expert validation questionnaires, material expert validation questionnaires, and guidance and counseling student response questionnaires. The data obtained in the study were then analyzed using the percentage formula. The research analysis showed that the design expert obtained 92.2% in the validation test, which was in the very valid category. The results of the material analysis validation expert, with a percentage of 94.4%, were in the very valid category, and the results of the analysis of student responses, with a percentage of 98 %, are also in the very valid category. Based on these results, the information technology course module in guidance and counseling that was developed is in the valid category and is very feasible to develop.